2017
DOI: 10.1108/mrjiam-04-2016-0663
|View full text |Cite
|
Sign up to set email alerts
|

Frontline employee empowerment and perceived customer satisfaction

Abstract: Purpose-The purpose of this paper is to examine the influence of structural empowerment, psychological empowerment and intrinsic motivation on perceived customer satisfaction in contact centers. Design/methodology/approach-A questionnaire was conducted among 703 employees of a contact center. Data analysis was based on structural equation modeling. Findings-Structural empowerment results in higher levels of perceived customer satisfaction through psychological empowerment and intrinsic motivation. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 63 publications
3
10
0
Order By: Relevance
“…The principal objective of this article was to test the impact of employee empowerment, employee training and teamwork on employee motivation at public universities in the northern region of Malaysia. The results revealed that employee empowerment has a significant relationship with employee motivation, and it matches a number of past researches and Maslow's hierarchy of needs theory (Caniëls, Neghina, & Schaetsaert, 2017;Proenca, Torres, & Sampaio, 2017) which confirmed that empowering employees was a significant factor in predicting their levels of motivation. Tutar et al (2011) examined the effect of empowerment on employee motivation and found that empowering employees at the workplace exerts a significant positive effect on their motivation.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…The principal objective of this article was to test the impact of employee empowerment, employee training and teamwork on employee motivation at public universities in the northern region of Malaysia. The results revealed that employee empowerment has a significant relationship with employee motivation, and it matches a number of past researches and Maslow's hierarchy of needs theory (Caniëls, Neghina, & Schaetsaert, 2017;Proenca, Torres, & Sampaio, 2017) which confirmed that empowering employees was a significant factor in predicting their levels of motivation. Tutar et al (2011) examined the effect of empowerment on employee motivation and found that empowering employees at the workplace exerts a significant positive effect on their motivation.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…Access to resources and organizational support may be necessary for the successful accomplishment of the activities. Opportunities for training and development, as well as rewards that value individual contributions and role clarity, provide guidance and direction for decision making (Spreitzer, 1995, 1996, 2008; Melhem, 2004; Laschinger et al , 2004; Cho and Faerman, 2010; Voegtlin et al , 2015; Proença et al , 2017).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…In this sense, the empowerment of call centers’ employees, and the implication of autonomy and knowledge about work-related situations, may increase their sense of responsibility and capacity to better respond to customer needs (Kim, 2007; Ayupp and Chung, 2010; Kassim et al , 2012; Shahril et al , 2015; Proença et al , 2017). According to Ongori (2009) and Isimoya and Bakarey (2013), it is important to allow contact employees to have the autonomy, self-control and job discretion to achieve the efficiency and effectiveness of services.…”
Section: Customer Satisfaction Empowerment and Job Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations